Los factores socioeconómicos y su incidencia en la tuberculosis en la comunidad puertas negras en el Cantón Babahoyo, Provincia Los Ríos periodo septiembre 2017 a febrero 2018 - Mayorga Cruz, Clemente Jerry (2018)
Introduction. - Tuberculosis (TB) is a social disease that, due to its link with poverty, mainly affects the developing countries and the most vulnerable sectors of the developed countries, which makes its control and eradication difficult. Objective. - Demonstrate how the socio-economic factor in the manifestation of tuberculosis is related to the inhabitants of the Puerta Negra citadel of the Babahoyo canton Methodology: descriptive, non-experimental, field and cross-sectional study, with a qualitative-quantitative approach. The sample was 35 people, by intentional non-probabilistic sampling. Scientific observation techniques were applied, surveys to collect the information. Results: It is demonstrated that of our population of 300 inhabitants of the sector, 12% is affected with this disease being 12% according to data obtained through the application of our survey. the knowledge of the symptoms of this disease, giving us as results that 90% of people have a total ignorance of the symptoms of this disease while on the other hand there is a 10% of people with knowledge of these symptoms and that the 37 of the people surveyed stated that older adults are more susceptible to catching the koch bacillus, while 63% of this group believe that it only affects people who consume cigarettes and are in contact with other risk factors. Conclusions - According to 85% of the respondents, they say that tuberculosis has an intimate relationship with socioeconomic factors and more in this sector that is marginal urban and has only one health center that does not cover all of their basic health needs.